Ultraviolet photodetection of flexible ZnO nanowire sheets in polydimethylsiloxane polymer - Liu, Jinzhang; Motta, Nunzio; Lee, Soonil (Beilstein Journal of Nanotechnology, 2012)
ZnO nanowires are normally exposed to an oxygen atmosphere to achieve high performance in UV photodetection. In this work we present results on a UV photodetector fabricated using a flexible ZnO nanowire sheet embedded in polydimethylsiloxane (PDMS), a gas-permeable polymer, showing reproducible UV photoresponse and enhanced photoconduction. PDMS coating results in a reduced response speed compared to that of a ZnO nanowire film in air. The rising speed is slightly reduced, while the decay time is prolonged by about a factor of four. We conclude that oxygen molecules diffusing in PDMS are responsible for the UV photoresponse.
Keywords: permeable polymer; photoresponse; polydimethylsiloxane; UV photodetection; ZnO nanowires